2018
DOI: 10.1080/01443615.2018.1460583
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and sites of pelvic adhesions in women with post-caesarean infertility

Abstract: This cross-sectional study was designed to evaluate the incidences and sites of pelvic adhesions in women with post-caesarean unexplained infertility. This study was conducted at the Tanta University Hospitals in the period from August 1 2015 to July 31 2016. The enrolled patients were assessed by a diagnostic laparoscopy for the presence and sites of abdominal and pelvic adhesions. Pelvic adhesions were found in 98 cases (73.13%) and the remaining 36 cases (26.87%) were free of adhesions. Adhesions were tubal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…We investigated the correlation of adhesions to number of cesarean deliveries, where no correlation was found with increased number of CD. This finding agrees with Dawood et al who found no correlation to number of CD [7]. This finding is not in agreement with the results of other studies which found that not only the incidence of adhesions increase with repeat CD but also the density of adhesions increase [3,12].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We investigated the correlation of adhesions to number of cesarean deliveries, where no correlation was found with increased number of CD. This finding agrees with Dawood et al who found no correlation to number of CD [7]. This finding is not in agreement with the results of other studies which found that not only the incidence of adhesions increase with repeat CD but also the density of adhesions increase [3,12].…”
Section: Discussionsupporting
confidence: 75%
“…Some studies reported that adhesions were increased with increasing number of repeat cesarean sections and led to more surgical difficulties [4]. Other studies reported adhesion formation with a rate of 24.7% after the first cesarean section while higher adhesion formation rates of up to 73.13% after the primary cesarean delivery were reported [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, peritoneal adhesions are commonly observed after abdominal and pelvic surgery, leading to chronic abdominal pain, intestinal obstruction, and female infertility ( Hol et al, 2019 ; Tang et al, 2020 ). And pelvic adhesions resulting from gynecologic surgery may also cause chronic pelvic pain, small bowel obstruction, and female infertility ( Al-Jabri and Tulandi, 2011 ; Dawood and Elgergawy, 2018 ). Besides, tendon adhesions not only cause dysfunction and pain, but also usually require surgical intervention to loosen ( Liu et al, 2013 ; Cai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…[1,2,4] Pelvic adhesions are held responsible for more than 20% of secondary female infertility and known to increase the risk of ectopic pregnancy. [1,13,14] The most fearsome and life-threatening complication of abdominal adhesions is the intestinal obstruction. More than half of all small bowel obstructions are caused by intra-abdominal adhesions.…”
Section: Discussionmentioning
confidence: 99%